Input switched closed-loop single phase SEPIC controlled rectifier with improved performances - Arifin, Md. Shamsul; Alam, Mohammad Jahangir (International Journal of Electrical and Computer Engineering (IJECE), 2021)
DC power supply has become the driving source for some essential modern applications. Thereby, DC power conditioning has become a significant issue for engineers. Typically used rectifiers associated with a bridge structure is nonlinear in nature. Thereby, the current at input side of the rectifier contains harmonics, which also flow through the power line. The presence of harmonics causes several interruptions and reduce power quality. In this regard, a new close loop SEPIC controlled rectifier is proposed in this paper. The conventional scheme is arranged with a rectifier connected to a DC-DC converter, which is an open loop system. Consequently, such system cannot regulate voltage at load varying condition. The proposed SEPIC controlled rectifier can regulate voltage under load varying condition for a wide range. Additionally, the performance in terms of total harmonic distortion (THD) of input current and power factor at AC side are also within satisfactory range for the closed loop configuration. The controlled rectifier has four operating phases associated with switching states and input voltage polarity. The close loop configuration also incorporates a current and a voltage loop at the feedback path. The comparative studies have been performed among the proposed closed loop construction, the open-loop structure as well as the conventional construction. The effectiveness of the proposed controlled rectifier is verified in terms of THD and input power factor considering the results obtained from simulation.